Exploring Students’ Willingness to Communicate (WTC) in Indonesian EFL Classroom (Proceedings of English Linguistics and Literature, 2022)
When the goal of English language teaching is categorized as for communication purposes, then it is essential to investigate students’ willingness to communicate (WTC). This research aimed to find out the students’ WTC in the EFL classroom. The researchers conducted descriptive research to compile the findings. The subjects were sixth-semester English Education students at Universitas Negeri Makassar, Indonesia. Purposive sampling was applied to gather data from a sample of 25 students. A questionnaire was used as a research instrument, which consisted of 27 question items, all related to the student's willingness to participate in communication inside the classroom. This research found that the students' WTC were classified into four categories: (1) definitely not willing, (2) probably not willing, (3) probably willing, and (4) definitely willing. Those scales operationalized WTC in four basic skill areas: speaking, reading, writing, and comprehension. It is found that most of the students were in the category of "probably willing" to "definitely willing" to show their WTC in the EFL classroom, which means that they mostly have positive communication behaviors and meet language learning targets. In addition, by measuring and promoting the WTC model in the EFL context, it is possible to better understand how students communicate and learn the language in realworld settings, predict what they will do when they communicate, and enhance how students use language in an EFL context.